The relationship between the living lab approach and successful implementation of healthcare innovations: an integrative review - Sylvia J van der Burg-Vermeulen; Nina Zipfel; Carel T J Hulshof; Angela G E M de Boer; Bedra Horreh (BMJ Open)
Objectives The concept of living labs as a research method to enhance participation of end-users in the development and implementation process of an innovation, gained increasing attention over the past decade. A living lab can be characterised by five key components: user-centric, cocreation, real-life context, test innovation and open innovation. The purpose of this integrative literature review was to summarise the literature on the relationship between the living lab approach and successful implementation of healthcare innovations.Methods An integrative literature review searching PubMed, EMBASE, PsycINFO and Cinahl databases between January 2000 and December 2019. Studies were included when a living lab approach was used to implement innovations in healthcare and implementation outcomes were reported. Included studies evaluated at least one of the following implementation outcomes: acceptability, adoption, appropriateness, feasibility, fidelity, implementation cost, penetration or sustainability. Quality was assessed based on a tool developed by Hawker et al.Results Of the 1173 retrieved articles, 30 studies were included of which 11 of high quality. Most studies involved a combination of patients/public (N=23) and providers (N=17) as key stakeholders in the living lab approach. Living lab components were mostly applied in the development phase of innovations (N=21). The majority of studies reported on achievement of acceptability (N=22) and feasibility (N=17) in terms of implementation outcomes. A broader spectrum of implementation outcomes was only evaluated in one study. We found that in particular six success factors were mentioned for the added-value of using living lab components for healthcare innovations: leadership, involvement, timing, openness, organisational support and ownership.Conclusions The living lab approach showed to contribute to successful implementation outcomes. This integrative review suggests that using a living lab approach fosters collaboration and participation in the development and implementation of new healthcare innovations.PROSPERO registration number CRD42020166895.